2022
DOI: 10.5423/ppj.oa.01.2022.0005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Pathogenicity of Lasiodiplodia theobromae Causing Black Root Rot and Identification of Novel Sources of Resistance in Mulberry Collections

Abstract: Black root rot (BRR) caused by Lasiodiplodia theobromae is an alarming disease of mulberry that causes tremendous economic losses to sericulture farmers in India and China. Successful control of this disease can be attained by screening germplasm and identifying resistant sources. Seventy four diseased root samples were collected from farmer’s fields belonging to four major mulberry growing states of South India. Based on morpho-cultural and scanning electron microscopy studies, 57 fungal isolates were charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…The results revealed that genotypes Kanva 2, Kokuso 21 and Rokokayaso were resistant against cutting rot disease. Similar results have been reported by Belaghihalli et al, (2022) [4] where in Kanva-2 belonging to Morus indica possessed resistance against Black Root Rot caused by Lasiodiplodia theobromae. Hongthongdaeng (1987) [3] reported that genotypes-Kokuso 21 and Rokokayoso from Morus multicaulis exhibited resistance towards root rot disease.…”
Section: Discussionsupporting
confidence: 90%
“…The results revealed that genotypes Kanva 2, Kokuso 21 and Rokokayaso were resistant against cutting rot disease. Similar results have been reported by Belaghihalli et al, (2022) [4] where in Kanva-2 belonging to Morus indica possessed resistance against Black Root Rot caused by Lasiodiplodia theobromae. Hongthongdaeng (1987) [3] reported that genotypes-Kokuso 21 and Rokokayoso from Morus multicaulis exhibited resistance towards root rot disease.…”
Section: Discussionsupporting
confidence: 90%
“…In inoculation experiments, fungal isolates obtained from plant samples collected from different locations have reported differences in pathogenicity due to species differences, variations in the degree of virulence of the fungal isolates and environmental effects such as temperature and pH (Lu et al, 2018). As reported by Gnanesh et al (2022), out of 20 isolates of Lasiodiplodia theobromae isolated from mulberry plants infected with black root rot disease, 16 were highly virulent and four isolates were less virulent despite being inoculated on susceptible mulberry genotypes.…”
Section: Discussionsupporting
confidence: 53%
“…In inoculation experiments, fungal isolates obtained from plant samples collected from different locations have reported differences in pathogenicity due to species differences, variations in the degree of virulence of the fungal isolates and environmental effects such as temperature and pH(Lu et al, 2018). As reported byGnanesh et al (2022), out of 20 isolates of Lasiodiplodia theobromae isolated from mulberry plants infected with black root rot disease, 16 were highly virulent and four isolates were less virulent despite being inoculated on susceptible mulberry genotypes.For example, according to Lu et al (2018), 38 isolates of Colletotrichum, isolated from anthracnose-infected tea leaves have reported pathogenicity differences due to the presence of two Colletotrichum spp., temperature range prevailed in the sampling F I G U R E 8 Lesion developed on stems of cinnamon plants inoculated with fungal isolates by cut and paste method, 3 weeks after inoculation (a) and callus-like structure developed 3 months after inoculation (b).TA B L E 2 Details of the fungal isolates and their combinations inoculated by cut and paste method to field-grown plants and the reisolated fungal isolates from the inoculated-stems.…”
mentioning
confidence: 91%
“…They generally display a high tolerance towards drought, pollution, and poor soil quality. As a result, they are distributed across a wide range of tropical, sub-tropical, and temperate zones in Asia, Europe, North America, South America, and Africa [3,4]. The Morus genus encompasses a total of 24 species within areas with a Mediterranean climate [5].…”
Section: Introductionmentioning
confidence: 99%